Baroque and mysticism – hypertrophy of thoughts and emotions? - Matuszewski, Krzysztof (Hybris, 2016)
In mysticism, I am mostly interested in emanations of some type of intensity of existence, which abstracts from the biological one. Revoking a treaty with time results in a puzzling personal experience, the story of which can be treated as an existential lesson. In mysticism, the truth becomes known through faith. It finds its source in love, which is the soul’s response for the salutary love of God directed at it. As a refusal of the demands of human nature, mysticism offers an entrance into the realm of the spirit and transcendence. The latter is approached by man through a sacrifice of love, which cleanses him of the ontological stain and guilt. The first stage of this peregrination is purification. It is an act of conscience stimulated by the vision of Christ’s passion, foreseeing death and inevitable Judgement. Purification is an encouragement for contrition and responsibility going beyond the temporal limits. In the second stage of the journey to God (illumination), a prayer for grace of life under the aegis of the cross substitutes the lament over oneself. It will be a life of humility, contemplation and doloristic imitation, crowned with love understood as following the intention of God.